2016
DOI: 10.1183/13993003.01721-2015
|View full text |Cite
|
Sign up to set email alerts
|

Tele-monitoring of ventilator-dependent patients: a European Respiratory Society Statement

Abstract: The estimated prevalence of ventilator-dependent individuals in Europe is 6.6 per 100 000 people. The increasing number and costs of these complex patients make present health organisations largely insufficient to face their needs. As a consequence, their burden lays mostly over families. The need to reduce healthcare costs and to increase safety has prompted the development of tele-monitoring for home ventilatory assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
116
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 112 publications
0
116
0
8
Order By: Relevance
“…Among COPD patients, evidence was also inconclusive where RPM was found to be an economically attractive option in some studies but not in others [6,[18][19][20][21][22][23]. A number of studies also reported the need for more research [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Among COPD patients, evidence was also inconclusive where RPM was found to be an economically attractive option in some studies but not in others [6,[18][19][20][21][22][23]. A number of studies also reported the need for more research [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement and research is needed before considering telemonitoring a real advancement at the service of patients with NMD on HMV [101, 109]. …”
Section: Home Care Management Of Long-term Noninvasive Ventilationmentioning
confidence: 99%
“…Thus, ideally, telehealth could be a key strategy in the management of HMV patients, representing a way for increasing health care access to these patients with special needs who are usually highly unfavorable to hospitalization, in an effort of providing more personalized care [101]. However, in a recent study published by Chatwin et al [102], the addition of telemonitoring to standard care did not lengthen the time to the next acute hospital admission and did not improve HRQOL of chronic respiratory patients.…”
Section: Home Care Management Of Long-term Noninvasive Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Ambrosino et al explained that the following four concepts must be considered before using technology for follow-up or to improve treatment: 1) it should improve access and reduce cost; 2) it should be suitable for care of chronic conditions (including global health status); 3) it should maintain contact with a reference hospital; and 4) it should provide education. 2 Sleep-disordered breathing (SDB), in terms of both patient characteristics and the processes applied, probably represents a clinical area were telemedicine could 2 Villanueva et al play a pivotal role. 3 In obstructive sleep apnea (OSA), for example, there is scope for assistance in ensuring adequate treatment, including sleep hygiene and continuous positive airway pressure (CPAP) compliance, the latter of which is an essential component of effective treatment.…”
Section: Introductionmentioning
confidence: 99%